Simultaneous Percutaneous Interventional Treatment of Atrial Septal Defects and Pulmonary Valve Stenosis in Children Under the Guidance of Transoesophageal Echocardiography Alone: Preliminary Experiences - Lu, Xuning; Wen, Ping; Liu, Yuhang; Zhu, Quanwei; Wang, Ning (Frontiers in Cardiovascular Medicine, 2022)
Objective To investigate the efficacy and safety of simultaneous percutaneous interventional treatment of atrial septal defects (ASDs) and pulmonary valve stenosis (PS) in children under the guidance of transoesophageal echocardiography (TEE) alone. Methods Eleven children with ASD combined with PS who were treated at our hospital between March 2015 and March 2019 were recruited, including 4 males and 7 females. Preoperative transthoracic echocardiography showed that all patients had type II ASDs of the foramen ovale subtype, with a maximum diameter of 12.9 ± 2.7 mm (9.0–18.0 mm). The guiding principle of septal occluder selection is that the diameter of the occluder should be 2–4 mm larger than the maximum diameter of the ASD. The pressure gradient across the pulmonary valve in patients with PS was 54.7 ± 5.8 mmHg (47.0–64.0 mmHg), and a balloon with a diameter 1.2–1.4 times the diameter of the pulmonary valve annulus was used for dilatation. Effective dilatation was repeated 2–3 times. All children underwent ASD occlusion and PS balloon dilatation through the femoral vein under TEE guidance without radiation or contrast agents. The patients underwent PS balloon dilatation first, followed by ASD occlusion. The treatment effect was evaluated by TEE immediately after the procedure, and the patients were followed up regularly. Results All patients underwent successful simultaneous ASD occlusion and PS balloon dilatation through the femoral vein under the guidance of TEE alone. The pressure gradient across the pulmonary valve immediately after the procedure was 21.3 ± 1.8 mmHg (19.0–25.0 mmHg) (P < 0.01). No shunt was detected at the atrial septum level. The patients were followed for 3.0 ± 1.4 years (1.0–5.0 years) after the procedure. The atrial septal occluders were in the normal position in all of the patients, and there was no arrhythmia, hemolysis, or residual shunting. The pressure gradient across the pulmonary valve at 1 month after the procedure was 18.5 ± 3.3 mmHg (P < 0.01). Conclusion Simultaneous percutaneous interventional treatment of ASD and PS in children under the guidance of TEE alone is not only safe and effective but also prevents trauma caused by extracorporeal circulation and surgical incision and damage caused by X-ray and contrast agents. The surgical sequence included first performing PS balloon dilatation, followed by ASD occlusion.